Položaj in pravne možnosti ločitvenih upnikov v postopku prisilne poravnave - Plavšak, Nina (Podjetje in delo, 2013)
The article deals with legal position of holders of secured claims in financial restructuring proceedings. Neither initiation of financial restructuring proceedings nor confirmed compulsory settlement affects secured claims. Therefore legal position of holders of secured claims remains unchanged.
Keywords: prisilna poravnava; terjatve; upniki; zavarovanje